PELATIHAN BUILDING INFORMATION MODELLING BERBASIS TEKLA STRUCTURES PADA SISWA SEKOLAH MENENGAH KEJURUAN KELAS XI DI KABUPATEN MOJOKERTO - Sarasanty, Diah; Tri Asmorowati, Erna; Nizar Zulfika, Dicki (Universitas Mataram, 2024)
Vocational High School (SMK) graduates contributed the most to the percentage of TPT (Open Unemployment Rate) as of August 2022 of 5.86% or 8.42 million people. The importance of increasing the involvement of partners in the world of work in designing and managing learning in vocational schools and developing the potential of students' abilities and expertise that are in line with opportunities to work in the world of work and/or entrepreneurship can reduce the TPT score. The results of direct observations at schools and confirmed based on the provisions of BSKAP 033/H/KR/2022, the learning achievements of students have not achieved their competencies in either phase E or F, namely regarding the ability to model 3D pictorial projections using BIM technology. The purpose of this PKM in the field of BIM applications is to improve students' skills in applying Building Information Modeling in achieving 3D modeling abilities and competencies. The empowerment method applied is in the form of training and mentoring of BIM applications in 3D modeling of construction buildings to improve the skills of partners related to drawing 3D building structures with BIM technology integrated with software. From the results of the initial and final assessment analysis, it was found that there was an increase in partner skills related to drawing 3D building structures with BIM technology integrated with software of ≥ 70% based on the performance of the 3D modeling simulation that was built after participating in the training as well as an increase in skills in creating informative construction design visualizations with software of ≥ 70%.